Solar energy potential in the Kingdom of Saudi Arabia: a comparative analysis, assessment and exploitation for power generation - Aldabesh, Abdulmajeed (2016)
This research investigates the potential for employing solar energy as a sustainable power generation source in the Kingdom of Saudi Arabia (KSA). The work maps the availability of solar energy throughout the country, and investigates the feasibility of implementing the technology at two case study locations. These are the existing power generation grid sites of Wadi Aldawasir (located 20° 23′ 22.00″ N 45° 12′ 32.00″ E), and Shuaibah (located 20° 37′ 22.84″ N 39° 33′ 44.02″ E). The first case study site, Wadi Aldawasir, covers an area of 48,900 m2, where parabolic trough solar thermal technology is proposed for power generation. The second case study site, Shuaibah power plant is one of the largest desalination and fossil fuel plants in the world with a 1,030,000 m3/ day capacity. Both case studies were assessed in terms of site specifications with selection based on Direct Normal Irradiation (DNI). A feasibility study examining Concentrated Solar Power (CSP) potential was conducted for both locations, with analysis of weather data, particularly monthly and annual, global horizontal and beam normal irradiation data. From these data, a reasonable estimate of CSP potential, and viability of the technology was determined. Simulation was then performed using Solar Advisor Model (SAM) and Renewable Energy Technology Screen (RETScreen) software, taking into account the location weather data, (DNI, dry-bulb and dew-point temperatures, relative humidity, barometric pressure, and wind speed), technical specification, (solar field, Solar Multiple (SM) Solar collector Assemblies (SCAs), power cycle and thermal storage) and economic parameters (energy unit cost, maintenance, etc.). Simulation evaluated annual energy performance (solar radiation resource of the solar field, electrical energy delivered by solar thermal plant, system losses, required solar field area), levelised cost of unit of power generated, CO2 emissions savings, and other financial feasibility indicators. The work shows that the energy yield of the new solar power plants using proposed CSP technology in both case studies is feasible.